2008
DOI: 10.1021/ct800277a
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Spin-State Energies for Iron Complexes

Abstract: A critical assessment of the OPBE functional is made for its performance for the geometries and spin-states of iron complexes. In particular, we have examined its performance for the geometry of first-row transition-metal (di)halides (MnX2, FeX2, CoX2, NiX2, CuX, X=[F, Cl]), whose results were previously [J. Chem. Theory Comput. 2006, 2, 1282] found to be representative for a much larger and more diverse set of 32 metal complexes. For investigating the performance for spin ground-states of iron complexes, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
405
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 354 publications
(435 citation statements)
references
References 78 publications
28
405
2
Order By: Relevance
“…Previous validation studies have shown the validity of the OPBE functional for the spin-state splittings of iron complexes. [51][52][53][54] The comparison between UB3LYP and UOPBE spin ground states indicates that same qualitative pictures are obtained with the two functionals. The same conclusion was drawn by de Visser et al when comparing the spin state splittings obtained using the UB3LYP, UBLYP, UB3PW91, and TPSS functionals.…”
Section: Computational Detailssupporting
confidence: 55%
“…Previous validation studies have shown the validity of the OPBE functional for the spin-state splittings of iron complexes. [51][52][53][54] The comparison between UB3LYP and UOPBE spin ground states indicates that same qualitative pictures are obtained with the two functionals. The same conclusion was drawn by de Visser et al when comparing the spin state splittings obtained using the UB3LYP, UBLYP, UB3PW91, and TPSS functionals.…”
Section: Computational Detailssupporting
confidence: 55%
“…[31] For example, whereas the parent compounds Fe(T b ) 2 and Fe(T c ) 2 2þ showed transition temperatures for the low-spin to high-spin switch above room temperature, placing a methyl group at the 3-position leads directly to high spin at low temperatures; instead, placing a methyl group at the 4-or 5-position has hardly an effect. We studied these complexes as well, [31] at the OPBE/TZP level, [32] and found that in general there was good agreement between the computed spin-state splittings at 0 K and the experimentally observed (or absent) SCO-behavior. Moreover, the computed and experimental M€ ossbauer parameters agreed well, and based on them, we were able to predict [31] that the complex with hydrotris(3-azo-indazol-1-yl)borato ligands (see Fig.…”
Section: Spin-crossover Compoundsmentioning
confidence: 64%
“…A combined experimental and theoretical endeavor (e.g., CECAM workshop) is needed to bring forward such a database of complicated systems. A number of systems are already known such as, for example, the spin states of Fe II -porphyrin with an axial histidine (or models for it); [3] the structurally similar monopyridylmethylamine Fe II (amp) 2 Cl 2 and dipyridylmethylamine Fe II (dpa) 2 2þ complexes with opposite spin groundstates; [32] Fe III -aryl porphyrins with different halide substitutions and different spin states; [37] Mn-oxo corrole and corrolazine. [8] However, until these are combined into a general database of complicated spin-state systems, the field does not advance and it will be difficult to value and validate new computational methods such as Deeth's LFMM method or new density functionals, let alone to give a rigorous estimate of the viability/validity of results obtained for a particular system.…”
Section: Discussionmentioning
confidence: 99%
“…Another nomenclature to annotate spin state uses singlet, triplet and quintet for the iron(II) ion or doublet, quartet and sextet for the iron(III) ion. The correspondence between the HS/LS states and these spin states for various iron-containing compounds can be found in the literature (Porro et al , 2009; Swart, 2008). …”
Section: Resultsmentioning
confidence: 90%